Simplified matching and tuning experimental receive coils for low-field NMR measurements. (March 2015) - Andris, Peter; Dermek, Tomáš; Frollo, Ivan
Highlights: The theoretical circuit analysis performed – Fig. 1, Eqs. (1)–(10). The optimization procedure for matching the coil – Eq. (9). The theoretical analysis of matching and tuning performed – Fig. 2. The noise spectral analysis performed – Fig. 3. The arrangement of the coil tuning utilizing the noise – Fig. 4. Results of the experiments – Fig. 5. Abstract: This article describes theoretical and practical results of experiments with home-made receive coils for an NMR scanner. A receive coil must ensure good sensitivity of the whole receiving chain, therefore the qualities of the coil are analysed together with a preamplifier. The coil must be tuned to the operating frequency of the scanner and matched to the input resistance of the preamplifier for effective processing of the induced signal. A technique for calculating matching device parameters using an optimization procedure is presented. The accuracy of the tuning and matching is analysed in the article and documented in figures. A technique for tuning the coils utilizing the spectral qualities of the noise produced by the receive coil or flowing through it is presented. The results are documented in figures for two coils and compared with assumed theoretical curves. The qualitative as well as the quantitative agreement is good. It has been proved that by fulfilling some conditions, accurate matching is not necessary and the noise spectrum can be utilized for tuning a receive coil.